Efin Recruiters: at the crossroads of the Indian RPO Industry. Issue 1 (27th March 2018) - Parameswar, Nakul; Singh, Ashwani; Malik, Rajat; Dhir, Sanjay
Abstract : Subject area: Strategic Management. Study level/applicability: Master of Business Administration/Executive Program in Management Level. Case overview: Rajat Malik started eFin Recruiters in January 2015 an RPO firm solely catering to the finance domain. Positioning eFin Recruiters in a niche domain created serious challenges to be tackled. Rajat was contemplating leveraging the Indian Government's Startup India campaign launched on January 16, 2016 to his advantage to scale up eFin Recruiters' operations by 400 per cent and compete with large established players in the RPO industry. Complacency and anticipated retaliatory action by competitors against eFin Recruiters' positioning in the niche domain were a huge impediment in eFin Recruiters' path to exponential growth. Expected learning outcomes: This case will enable students to understand the concepts of industry analysis, strategic positioning from the view of an entrepreneurial firm and business level strategy. This case acts as a medium to integrate entrepreneurship and strategy which is of utmost relevance. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS: 11: Strategy.